Preparation method and application of long-endurance fast-charging MXene solid potassium ion supercapacitor electrode material
By using high crystallinity and large pitch MXene (SN-Ti3C2) electrode material with high crystallinity and large spacing in solid potassium ion supercapacitors, the problem of structural damage caused by potassium ion embedding is solved, and the high energy density and rate performance is improved, with the characteristics of long battery life and fast charging.
Patent Information
- Application Number
- CN202411430555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The solid potassium ion supercapacitor has a large ion radius of potassium ions that cause the structure of the electrode material to be damaged and the energy density decreases. The contact surfaces between the solid electrolyte and the electrode material have interface resistance and low ionic conductivity, which affects the energy density and rate performance.
A gentle liquid etching method of H2SO4 plus NH4F was used to prepare high crystallinity and large spacing MXene (SN-Ti3C2) electrode material with high crystallinity and large spacing, improving its surface area and structural integrity, increasing the number of active sites and improving antioxidant capacity.
It achieves high energy density and excellent rate performance, has the characteristics of long battery life and fast charging, and improves the stability and safety performance of electrochemical cycles.
Smart Images

Figure CN119889942A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state potassium ion supercapacitors, and in particular relates to a preparation method and application of a long-life fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material. Background Art
[0002] Potassium ion supercapacitors can be used as auxiliary power sources for electric vehicles and form hybrid power systems with batteries. Due to its high power density and fast charging and discharging characteristics, it can provide a large amount of energy for electric vehicles in a short period of time to meet high power requirements such as acceleration and climbing. The wide application of aqueous liquid phase potassium ion supercapacitors is limited by problems such as low operating voltage window and safety hazards caused by dendrites. Solid-state potassium ion supercapacitors support higher voltage windows and have good safety, and are one of the future development directions. However, due to the large ionic radius of potassium ions, repeated embedding leads to structural destruction of electrode materials, a sharp drop in energy density, and large interface resistance and low ionic conductivity at the contact surface between solid electrolyte and electrode materials, which seriously affect the energy density and rate performance of solid-state potassium ion supercapacitors. Therefore, it is necessary to develop new electrode materials to improve related problems.
[0003] MXene materials are predicted to be a new generation of energy storage materials and an ideal carbon electrode substitute material due to their two-dimensional structure similar to carbon materials, controllable layer structure, high specific surface area, rich controllable surface functional groups, excellent conductivity and good chemical stability. CN 117945402 A discloses a "method for preparing multilayer hexagonal pore MXene materials with carbon vacancy defects for aqueous potassium ion supercapacitors". The method puts dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder into a vacuum hot pressing sintering furnace, and hot presses and sinters them in a vacuum hot pressing sintering furnace with argon as a protective atmosphere, and then cools with liquid nitrogen to obtain a hexagonal carbon vacancy MAX phase Ti3AlC2; hexagonal pore MXene is prepared by microwave assisted etching to obtain a multilayer hexagonal pore MXene negative electrode material. The advantage is that the prepared multilayer hexagonal pore MXene directly captures potassium ions with large radius without serious deformation of its own volume. Moreover, the mass specific capacity of aqueous potassium ion supercapacitors has been greatly improved, and the mass specific capacity attenuation is small in long-cycle charge and discharge. However, this method uses MXene materials prepared by HF and HCl plus fluoride liquid phase method to etch and form multi-layer hexagonal pore MXene materials. The hexagonal pore structure can increase the specific surface area of MXene, providing more active sites for the storage of potassium ions in the electrolyte, but the material has a tight interlayer spacing and an incomplete crystal structure. The tight interlayer spacing is not conducive to the deintercalation of large-radius potassium ions, and the incomplete crystal structure is not conducive to ion diffusion and electron transfer; when used in solid-state potassium ion supercapacitors, it seriously limits the improvement of the energy density and rate performance of MXene in solid-state potassium ion supercapacitors. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method and application of a long-life fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material. The preparation process is simple, and the prepared MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material has good crystallinity and interlayer spacing, and can be used as an electrode material for a solid-state potassium ion supercapacitor, thereby enabling the solid-state potassium ion supercapacitor to have a larger voltage window, high energy density and excellent rate performance.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material, the specific steps are as follows:
[0007] (1) Preparation of MAX phase Ti3AlC2
[0008] Pure titanium powder, aluminum powder and ball-milled spherical graphite powder were placed in a vacuum hot-pressing sintering furnace in a molar ratio of 3.1:1.12:1.35, and hot-pressed sintering was performed in the vacuum hot-pressing sintering furnace with argon as the protective gas. The sintering temperature was 1500°C, the pressure head pressure of the vacuum hot-pressing sintering furnace was set to 15T, and the hot-pressing sintering time was 5h. After the hot-pressing sintering was completed, the MAX phase Ti3AlC2 was obtained by cooling the furnace.
[0009] (2) Preparation of long-life fast-charging MXene (SN-Ti3C2) electrode materials
[0010] 36 mL of a mixture of H2SO4 and NH4F was added to every 1 g of MAX phase Ti3AlC2, and the mixture was magnetically stirred at a constant temperature of 80°C in a constant temperature water bath. The MAX phase Ti3AlC2 was added to the mixture of H2SO4 and NH4F, wherein the molar ratio of H2SO4 to NH4F was 2:1. The mixture was sealed and stirred at a constant temperature of 80°C for 6 h. After ultrasonic stratification at room temperature for 1 h, the mixture was filtered and the filter cake was centrifugally washed with deionized water, filtered, and vacuum dried in a vacuum drying oven to obtain a long-life, fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material.
[0011] Furthermore, the power of the vacuum hot pressing sintering furnace is 50KW.
[0012] Furthermore, the diameter of the effective contact surface of the pressure head of the vacuum hot pressing sintering furnace is Φ75 mm.
[0013] Furthermore, the filling pressure of the argon protective atmosphere is 0.04 MPa.
[0014] Furthermore, the concentration of sulfuric acid was 3 mol·L -1 .
[0015] Furthermore, the rotation speed of the magnetic stirring is 600 r / min.
[0016] Furthermore, during centrifugal washing, the centrifugal speed was 3500 r / min and the centrifugal time was 20 min.
[0017] A long-life fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material is used as an electrode material in a solid-state potassium ion supercapacitor.
[0018] A long-life fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material is used as positive and negative electrode materials in solid-state potassium ion supercapacitors.
[0019] Furthermore, the preparation process of the solid-state potassium ion supercapacitor is as follows:
[0020] (1) Preparation of positive and negative electrode sheets
[0021] The prepared long-life fast-charging MXene (SN-Ti3C2), acetylene black and PVDF were mixed in a mass ratio of 9:0.5:0.5, ground for 30 minutes, and NMP solvent was added dropwise, and stirred evenly to form an electrode slurry; the electrode slurry was evenly coated on the carbon cloth, and then dried at 80°C for 24 hours, and cut to obtain the positive and negative electrode sheets of the long-life fast-charging MXene;
[0022] (2) Preparation of potassium ion solid electrolyte
[0023] Weigh KCl, K2S, Sb2S3, and S in a molar ratio of 1.1:3:1:2, mix and grind; then put them into an alumina corundum crucible, put the crucible into a vacuum sintering furnace, and sinter at a constant temperature of 550°C for 12 hours. Then, cool the furnace, take it out, grind it into powder, and obtain K3SbS3Cl potassium ion solid electrolyte;
[0024] (3) Assembly of solid-state potassium ion supercapacitors
[0025] The positive electrode sheet of long-life fast-charging MXene, the K3SbS3Cl potassium ion solid electrolyte and the negative electrode sheet of long-life fast-charging MXene are loaded and assembled in sequence to form a symmetrical solid-state potassium ion supercapacitor.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention adopts a mild H2SO4 plus NH4F liquid phase etching method to prepare a MXene (SN-Ti3C2) electrode material with high crystallinity and large spacing; compared with the HF and HCl methods, the high crystallinity enables the MXene (SN-Ti3C2) electrode material to have a more complete structure and increase its surface area; this increases the number of active sites and provides favorable conditions for the adsorption of potassium ions; secondly, the high crystallinity enables the MXene (SN-Ti3C2) electrode material to have fewer defects, reduces the attack targets of oxygen and water molecules, and improves the antioxidant capacity of the MXene (SN-Ti3C2) electrode material. The chemical cycle stability is improved; finally, the large spacing of MXene (SN-Ti3C2) electrode materials is conducive to full contact with the electrolyte, achieving a high number of potassium ion embedding, while alleviating the structural damage problem caused by the deintercalation of large-diameter potassium ions; the high crystallinity and large spacing of MXene (SN-Ti3C2) electrode materials have a complete structure, fewer defects and a large interlayer spacing; this increases the contact area between the electrolyte and the electrode material, improves the diffusion efficiency of potassium ions at the contact end face and the transfer rate of internal electrons, greatly improves the energy density and rate performance of MXene in solid-state potassium ion supercapacitors, and has the characteristics of long battery life and fast charging.
[0028] (2) The symmetrical solid-state potassium ion supercapacitor assembled by the present invention has good cycle stability under a large voltage window; the prepared solid electrolyte of sulfide-based ion conductor avoids the formation of dendrites and has good thermal stability; at the same time, it has a higher ionic conductivity, improves the diffusion efficiency of potassium ions in the electrolyte, and improves the performance and safety performance; this makes the solid-state potassium ion supercapacitor with high crystallinity and large spacing MXene (SN-Ti3C2) prepared by H2SO4 method as electrode pole piece have a broad application space. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 is the XRD diagram of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2 of the present invention (corresponding to Example 1, Comparative Example 1 and Comparative Example 2);
[0030] Figure 2 1 is the EIS graph of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2 of the present invention (corresponding to Example 1, Comparative Example 1 and Comparative Example 2);
[0031] Figure 3 is a SEM image of MXene (SN-Ti3C2) of the present invention (corresponding to Example 1);
[0032] Figure 4: is a GCD curve diagram of the MXene (SN-Ti3C2) solid-state potassium ion supercapacitor of the present invention (corresponding to Example 1);
[0033] Figure 5 is a SEM image of MXene (HF-Ti3C2) prepared by HF etching of the present invention (corresponding to Example 1);
[0034] Figure 6 : is a GCD curve diagram of the MXene (HF-Ti3C2) solid-state potassium ion supercapacitor of the present invention (corresponding to Example 1);
[0035] Figure 7 It is a SEM image of MXene (HN-Ti3C2) prepared by adding HCl to NH4F of the present invention (corresponding to Example 2);
[0036] Figure 8 It is a GCD curve diagram of the MXene (HN-Ti3C2) solid-state potassium ion supercapacitor of the present invention (corresponding to Example 2). DETAILED DESCRIPTION
[0037] Example 1
[0038] 1). Preparation of MAX phase Ti3AlC2
[0039] Pure titanium powder, aluminum powder and ball-milled spherical graphite powder were placed in a vacuum hot pressing sintering furnace according to a molar ratio of 3.1:1.12:1.35, and hot pressing sintering was performed in the vacuum hot pressing sintering furnace using argon as protective gas. The gas pressure of the argon protective atmosphere was 0.04MPa, the power of the vacuum hot pressing sintering furnace was 50KW, the diameter of the effective contact surface of the pressure head was Φ75mm, the sintering temperature was 1500℃, the pressure head of the vacuum hot pressing sintering furnace was set to 15T, and the hot pressing sintering time was 5h; after the hot pressing sintering was completed, the MAX phase Ti3AlC2 was obtained by cooling with the furnace;
[0040] 2). Preparation of long-life fast-charging MXene (SN-Ti3C2) electrode materials
[0041] ① Weigh 1 g of the MAX phase Ti3AlC2 prepared in step 1) for later use;
[0042] ② Prepare H2SO4-NH4F etching solution, the volume of the mixed solution is 36mL, and the molar ratio of H2SO4 to NH4F is 2:1;
[0043] Step 1: Prepare 36 mL of 3 mol·L -1 H2SO4 solution;
[0044] Step 2: Weigh 2 g of NH4F, pour into 36 mL of H2SO4 solution, stir on a stirrer at 450 r / min for 10 min until NH4F is completely dissolved;
[0045] ③ Pour 1g of MAX phase Ti3AlC2 prepared in step 1) into 36mL H2SO4-NH4F etching solution prepared in step 2)② within 5 minutes, seal, and perform constant temperature magnetic stirring in a constant temperature water bath for 6 hours, temperature: 80°C, speed: 600r / min; after ultrasonic stratification at room temperature for 1 hour, filter to remove H2SO4-NH4F etching solution; finally, add 30mL of deionized water and centrifuge at a speed of 3500r / min for 20 minutes to clean and remove impurities, and finally filter again and dry in a vacuum drying oven for 8 hours to obtain a long-life fast-charging MXene (SN-Ti3C2) electrode material;
[0046] 3). Preparation of solid-state potassium ion supercapacitor
[0047] (1) Preparation of positive and negative electrode sheets
[0048] The prepared long-life fast-charging MXene (SN-Ti3C2) electrode material, acetylene black and PVDF were mixed in a mass ratio of 9:0.5:0.5, then ground in an agate mortar for 30 minutes, NMP solvent was added dropwise, and stirred evenly to form an electrode slurry. The electrode slurry was evenly coated on the carbon cloth after ultrasonic cleaning and drying, and dried at 80°C for 24 hours, and the positive and negative electrode sheets of the long-life fast-charging MXene (SN-Ti3C2) were cut out to be 8 cm × 5 cm;
[0049] (2) Preparation of potassium ion (K3SbS3Cl) solid electrolyte
[0050] Weigh KCl, K2S, Sb2S3, and S in a molar ratio of 1.1:3:1:2, mix and grind; then put them into an alumina corundum crucible, put the crucible into a vacuum sintering furnace, and sinter at a constant temperature of 550°C for 12 hours. Then, take them out of the furnace after cooling, grind them into powder, and obtain a potassium ion (K3SbS3Cl) solid electrolyte for standby use;
[0051] (3) Assembly of solid-state potassium ion supercapacitors
[0052] The positive electrode sheet of long-life fast-charging MXene (SN-Ti3C2), the potassium ion (K3SbS3Cl) solid electrolyte and the negative electrode sheet of long-life fast-charging MXene (SN-Ti3C2) are loaded and assembled in sequence to form a symmetrical solid-state potassium ion supercapacitor.
[0053] like Figure 1As shown in the figure, the XRD patterns of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2 are compared. The (002) diffraction peak intensity of SN-Ti3C2 prepared in Example 1 is the strongest, the crystallinity is the highest, and the internal defects are relatively few, which is conducive to the improvement of the cycle stability of SN-Ti3C2; the (002) diffraction peak of SN-Ti3C2 has the largest deviation to a small angle, which indicates that it has a larger lattice spacing, which is conducive to the embedding and extraction of large-diameter potassium ions and improves the rate performance. Figure 2 As shown in the figure, comparing the EIS graphs of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2, SN-Ti3C2 has a smaller arc radius, a lower charge transfer resistance, and a higher slope in the high frequency region, and has a higher diffusion efficiency, which indicates that SN-Ti3C2 has higher electrical conductivity and ion diffusion efficiency. Figure 3 As shown in the SEM image of SN-Ti3C2, it can be seen that SN-Ti3C2 has a large interlayer distance, which is conducive to the deep penetration of the electrolyte and improves the energy density. Figure 4 As shown, from the GCD curve of SN-Ti3C2 at high current density, it can be seen that after 1000 cycles of charge and discharge, the capacity decays from 492.2F / g to 275.6F / g, and the capacity retention rate is 55.6%; the test results show that high-crystallinity large-pitch SN-Ti3C2 has excellent stability, high rate capability and high specific capacity in symmetrical solid-state potassium ion supercapacitors.
[0054] Comparative Example 1
[0055] 1). Preparation of MAX phase Ti3AlC2
[0056] Pure titanium powder, aluminum powder and ball-milled spherical graphite powder were placed in a vacuum hot pressing sintering furnace according to a molar ratio of 3.1:1.12:1.35, and hot pressing sintering was performed in the vacuum hot pressing sintering furnace using argon as protective gas. The gas pressure of the argon protective atmosphere was 0.04MPa, the power of the vacuum hot pressing sintering furnace was 50KW, the diameter of the effective contact surface of the pressure head was Φ75mm, the sintering temperature was 1500℃, the pressure head of the vacuum hot pressing sintering furnace was set to 15T, and the hot pressing sintering time was 5h; after the hot pressing sintering was completed, the MAX phase Ti3AlC2 was obtained by cooling with the furnace;
[0057] 2). Preparation of multilayer MXene (HF-Ti3C2) electrode materials by severe hydrofluoric acid etching
[0058] ① Weigh 1 g of the MAX phase Ti3AlC2 prepared in step 1) for later use;
[0059] ② Prepare HF etching solution with a mass concentration of 40% and a solution volume of 36 mL;
[0060] ③Put the HF etching solution into a constant temperature water bath for constant temperature magnetic stirring, the temperature is 80°C and the speed is 600r / min.
[0061] Pour 1g of MAX phase Ti3AlC2 into 36mL HF etching solution prepared in step 2)② within 5 minutes, seal, and perform constant temperature magnetic stirring in a constant temperature water bath for 6h, temperature: 80℃, speed: 600r / min; after ultrasonic stratification at room temperature for 1h, filter to remove HF etching solution; finally, add 30mL deionized water and centrifuge at a speed of 3500r / min for 20min to clean and remove impurities, finally filter again, and dry in a vacuum drying oven for 8h to obtain a multilayer MXene (HF-Ti3C2) electrode material;
[0062] 3). Preparation of solid-state potassium ion supercapacitor
[0063] (1) Preparation of positive and negative electrode sheets
[0064] The prepared multilayer MXene (HF-Ti3C2) electrode material, acetylene black and PVDF were mixed in a mass ratio of 9:0.5:0.5, then ground in an agate mortar for 30 minutes, NMP solvent was added dropwise, and stirred evenly to form an electrode slurry. The electrode slurry was evenly coated on the carbon cloth after ultrasonic cleaning and drying, and dried at 80°C for 24 hours, and 8cm×5cm multilayer MXene (HF-Ti3C2) positive and negative electrode sheets were cut out;
[0065] (2) Preparation of potassium ion (K3SbS3Cl) solid electrolyte
[0066] Same as Example 1;
[0067] (3) Assembly of solid-state potassium ion supercapacitors
[0068] A symmetrical solid-state potassium ion supercapacitor was assembled in the order of a positive electrode sheet of multilayer MXene (HF-Ti3C2), a potassium ion (K3SbS3Cl) solid electrolyte prepared in Example 1, and a negative electrode sheet of multilayer MXene (HF-Ti3C2).
[0069] like Figure 1 As shown in the figure, the XRD patterns of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2 are compared. The (002) diffraction peak intensity of HF-Ti3C2 prepared in Comparative Example 1 is the lowest, the crystallinity is the worst, and there are many internal defects, which is not conducive to the improvement of the cycle stability of HF-Ti3C2; the (002) diffraction peak of HF-Ti3C2 has the smallest deviation to a small angle, which means that it has a smaller lattice spacing, which is not conducive to the embedding and extraction of large-diameter potassium ions, and reduces the rate performance. Figure 2 As shown in the figure, comparing the EIS graphs of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2, HF-Ti3C2 has the largest arc radius, has a larger charge transfer resistance, and has a lower slope in the high frequency region, and has a lower diffusion efficiency, which indicates that HF-Ti3C2 has lower conductivity and ion diffusion efficiency. Figure 5 As shown in the SEM image of HF-Ti3C2, it can be seen that HF-Ti3C2 has a small interlayer distance, which is not conducive to the deep penetration of the electrolyte and reduces the energy density. Figure 6 As shown in the figure, from the GCD curve of HF-Ti3C2 at high current density, it can be seen that after 1000 cycles of charge and discharge, the capacity decays from 421.6F / g to 121.3F / g, and the capacity retention rate is 28.2%. The test results show that multilayer HF-Ti3C2 has poor stability and low specific capacity in symmetrical solid-state potassium ion supercapacitors, which is not ideal in the application of solid-state potassium ion supercapacitors.
[0070] Comparative Example 2
[0071] 1). Preparation of MAX phase Ti3AlC2
[0072] Pure titanium powder, aluminum powder and ball-milled spherical graphite powder were placed in a vacuum hot pressing sintering furnace according to a molar ratio of 3.1:1.12:1.35, and hot pressing sintering was performed in the vacuum hot pressing sintering furnace using argon as protective gas. The gas pressure of the argon protective atmosphere was 0.04MPa, the power of the vacuum hot pressing sintering furnace was 50KW, the diameter of the effective contact surface of the pressure head was Φ75mm, the sintering temperature was 1500℃, the pressure head of the vacuum hot pressing sintering furnace was set to 15T, and the hot pressing sintering time was 5h; after the hot pressing sintering was completed, the MAX phase Ti3AlC2 was obtained by cooling with the furnace;
[0073] 2). Preparation of multilayer MXene (HN-Ti3C2) electrode materials
[0074] ① Weigh 1 g of the MAX phase Ti3AlC2 prepared in step 1) for later use;
[0075] ②Prepare HCl-NH4F etching solution
[0076] Step 1: Prepare 36 mL of 9 mol·L -1 HCl solution;
[0077] Step 2: Weigh 2 g of NH4F, pour into 36 mL of HCl solution, stir on a stirrer at 450 r / min for 10 min until NH4F is completely dissolved;
[0078] ③ Slowly pour 1g of MAX phase Ti3AlC2 prepared in step 1) into 36mL HCl—NH4F etching solution within 5 minutes, seal, and perform constant temperature magnetic stirring in a constant temperature water bath for 6h, temperature: 80℃, rotation speed: 600r / min; then ultrasonic stratification at room temperature for 1h, filter to remove HCl—NH4F etching solution; finally, add 30mL of deionized water and centrifuge at a speed of 3500r / min for 20min to clean and remove impurities, finally filter again, and dry in a vacuum drying oven for 8h to obtain a multilayer MXene (HN-Ti3C2) electrode material.
[0079] 3). Preparation of solid-state potassium ion supercapacitor
[0080] (1) Preparation of positive and negative electrode sheets
[0081] The prepared multilayer MXene (HN-Ti3C2) electrode material, acetylene black and PVDF were mixed in a mass ratio of 9:0.5:0.5, then ground in an agate mortar for 30 minutes, NMP solvent was added dropwise, and stirred evenly to form an electrode slurry. The electrode slurry was evenly coated on the carbon cloth after ultrasonic cleaning and drying, and then dried at 80°C for 24 hours, and 8cm×5cm multilayer MXene (HN-Ti3C2) positive and negative electrode sheets were cut out;
[0082] (2) Preparation of potassium ion (K3SbS3Cl) solid electrolyte
[0083] Same as Example 1;
[0084] (3) Assembly of solid-state potassium ion supercapacitors
[0085] A symmetrical solid-state potassium ion supercapacitor was assembled in the order of a positive electrode sheet of multilayer MXene (HN-Ti3C2), a potassium ion (K3SbS3Cl) solid electrolyte prepared in Example 1, and a negative electrode sheet of multilayer MXene (HN-Ti3C2).
[0086] like Figure 1 As shown in the figure, the XRD patterns of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2 are compared. The (002) diffraction peak intensity of HN-Ti3C2 in comparative example 2 is lower than that of SN-Ti3C2 prepared by sulfuric acid method in Example 1, and there are a certain number of internal defects, which is not conducive to the improvement of the cycle stability of HN-Ti3C2; the (002) diffraction peak of HN-Ti3C2 is offset to a small angle in the middle but lower than that of SN-Ti3C2 prepared by sulfuric acid method in Example 1, which means that its lattice spacing is smaller than that of MXene material prepared by SN-Ti3C2 sulfuric acid method, and the mobility of large-diameter potassium ions is lower, which reduces the rate performance. Figure 2As shown in the figure, comparing the EIS graphs of HF-Ti3C2, HN-Ti3C2 and SN-Ti3C2, HN-Ti3C2 has a larger arc radius, a larger charge transfer resistance, and a lower slope in the high frequency region, and has a lower diffusion efficiency, which indicates that HN-Ti3C2 has lower conductivity and ion diffusion efficiency. Figure 7 As shown in the SEM image of HN-Ti3C2, it can be seen that HN-Ti3C2 has a certain amount of large interlayer distance, which is conducive to the deep penetration of the electrolyte and has a higher energy density. Figure 8 As shown, from the GCD curve of HN-Ti3C2 at high current density, it can be seen that after 1000 cycles of charge and discharge, the capacity decays from 470.1F / g to 165.3F / g, and the capacity retention rate is 35%; the test results show that multilayer HN-Ti3C2 has poor stability and high specific capacity in symmetrical solid-state potassium ion supercapacitors, and is less ideal in the application of solid-state potassium ion supercapacitors.
Claims
1. A method for preparing a long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material, characterized by: The specific steps are as follows: (1) Preparation of MAX phase Ti3AlC2 Pure titanium powder, aluminum powder and ball-milled spherical graphite powder were placed in a vacuum hot-pressing sintering furnace in a molar ratio of 3.1:1.12:1.35, and hot-pressed sintering was performed in the vacuum hot-pressing sintering furnace with argon as the protective gas. The sintering temperature was 1500°C, the pressure head pressure of the vacuum hot-pressing sintering furnace was set to 15T, and the hot-pressing sintering time was 5h. After the hot-pressing sintering was completed, the MAX phase Ti3AlC2 was obtained by cooling the furnace. (2) Preparation of MXene electrode materials with long battery life and fast charging For every 1 g of MAX phase Ti3AlC2, 36 mL of a mixture of H2SO4 and NH4F was added, wherein the molar ratio of H2SO4 to NH4F was 2:
1. The mixture was sealed and stirred at a constant temperature of 80°C for 6 h. After ultrasonic stratification at room temperature for 1 h, the mixture was filtered and the filter cake was centrifugally washed with deionized water, filtered, and vacuum dried to obtain a long-life, fast-charging MXene solid-state potassium ion supercapacitor electrode material.
2. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized in that: The power of the vacuum hot pressing sintering furnace is 50KW.
3. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized in that: The diameter of the effective contact surface of the pressure head of the vacuum hot pressing sintering furnace is Φ75mm.
4. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized in that: The filling pressure of the argon protective atmosphere is 0.04MPa.
5. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized by: The concentration of sulfuric acid used was 3 mol·L -1 .
6. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized by: The speed of magnetic stirring was 600 r / min.
7. The method for preparing the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 1 is characterized by: During centrifugal cleaning, the centrifugal speed is 3500r / min and the centrifugal time is 20min.
8. An application of the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material as claimed in claim 1 as an electrode material in a solid-state potassium ion supercapacitor.
9. Application of the long-life fast-charging MXene (SN-Ti3C2) solid-state potassium ion supercapacitor electrode material according to claim 1 as positive and negative electrode materials in solid-state potassium ion supercapacitors.
10. The use of the long-life fast-charging MXene solid-state potassium ion supercapacitor electrode material according to claim 8 as an electrode material in a solid-state potassium ion supercapacitor, characterized in that: The preparation process of the solid-state potassium ion supercapacitor is as follows: (1) Preparation of positive and negative electrode sheets The prepared long-life fast-charging MXene (SN-Ti3C2), acetylene black and PVDF were mixed in a mass ratio of 9:0.5:0.5, ground for 30 minutes, and NMP solvent was added dropwise, and stirred evenly to form an electrode slurry; the electrode slurry was evenly coated on the carbon cloth, and then dried at 80°C for 24 hours, and cut to obtain the positive and negative electrode sheets of the long-life fast-charging MXene; (2) Preparation of potassium ion solid electrolyte Weigh KCl, K2S, Sb2S3, and S in a molar ratio of 1.1:3:1:2, mix and grind; then put them into an alumina corundum crucible, put the crucible into a vacuum sintering furnace, and sinter at a constant temperature of 550°C for 12 hours. Then, cool the furnace, take it out, grind it into powder, and obtain K3SbS3Cl potassium ion solid electrolyte; (3) Assembly of solid-state potassium ion supercapacitors The positive electrode sheet of long-life fast-charging MXene, the K3SbS3Cl potassium ion solid electrolyte and the negative electrode sheet of long-life fast-charging MXene are loaded and assembled in sequence to form a symmetrical solid-state potassium ion supercapacitor.
Citation Information
Patent Citations
Preparation method for Mxenes colloid
CN106495210A
Preparation method and application of two-dimensional crystal MXene nanomaterial
CN109896524A
Oxygen atom in-situ doped MAX phase and in-situ doped MXene flexible membrane electrode material as well as preparation method and application thereof
CN113401904A
High-damping intelligent vibration attenuation sheet material and preparation method thereof
CN114874609A
High-entropy MXene material, high-entropy MAX phase material, preparation methods of high-entropy MXene material and high-entropy MAX phase material, electrode and battery
CN115745018A